2021
DOI: 10.31351/vol30iss1pp101-109
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Liver Function and Rh Blood Group between both Physiological and Pathological Neonatal Jaundice

Abstract: Abstract Backgrounds: Jaundice occurs in most newborn due to increased bilirubin concentration. Jaundice is observed during the first week after birth in approximately 60% of term neonates. A high level of bilirubin is neurotoxic and may cause neonatal kernicterus, auditory neuropathy or death. Objectives: to compare the Rh group compatibility, serum bilirubin (total and direct), serum albumin and several liver enzymes between physiological and pathological neonatal jaundice Materials and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…These results contradicted those found by Kamal and Hassan (2021) who revealed that gender influences the occurrence of jaundice in newborns, with male infants having a lower risk than female infants [26]. Various degrees of liver disease exist because ALT is restricted to the liver, unlike AST, which is abundant in other organs, such as kidneys, brain, and heart.…”
Section: The Levels Of Alt Ast Alp and Tsbmentioning
confidence: 70%
“…These results contradicted those found by Kamal and Hassan (2021) who revealed that gender influences the occurrence of jaundice in newborns, with male infants having a lower risk than female infants [26]. Various degrees of liver disease exist because ALT is restricted to the liver, unlike AST, which is abundant in other organs, such as kidneys, brain, and heart.…”
Section: The Levels Of Alt Ast Alp and Tsbmentioning
confidence: 70%